Third watch - McCaffrey, Anne (McCaffrey, Anne. Acorna series (Eos (Firm)), 2007)
Acorna's rebellious daughter risks everything in order to protect the universe from a mysterious plague-spreading enemy, an effort that is compromised by threats closer to home.